Peningkatan Karakter Siswa Kelas VIII SMP Santo Tarcisius Dumai Melalui Model Pembelajaran Problem-Based Learning (PBL) pada Materi Peran Roh Kudus - Dominikus Bria Tahu (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study aims to improve the character of 8th grade students of SMP Santo Tarcisius Dumai through the application of the Problem-Based Learning (PBL) learning model on the material of the Role of the Holy Spirit. This research was motivated by problems related to the low character of students in understanding and practicing the spiritual values contained in the material. The PBL model was chosen because it is considered capable of encouraging students to be active, critical, and collaborative in solving problems related to learning material, so that it is expected to increase understanding and practice of the character values taught. This research uses the Classroom Action Research method with a cycle that includes planning, action, observation, and reflection. The results of the study are expected to make a positive contribution to the development of student character through innovative and effective learning approaches.